The late age of print : everyday book culture from consumerism to control - Striphas, Theodore G. (Columbia University Press, 2009)
"Ted Striphas argues that, although the production and propagation of books undoubtedly have entered a new phase, printed works are still very much a part of our everyday lives. With examples from trade journals, news media, advertisements, and a host of other commercial and scholarly materials, Striphas tells a story of modern publishing that proves, even in a rapidly digitizing world, books are anything but dead."--Inside jacket.